Occupational Burnout Symptoms and Its Relationship With Workload and Fear of the SARS-CoV-2 Pandemic Among Hospital Nurses - Belji Kangarlou, Marzieh; Fatemi, Farin; Paknazar, Fatemeh; Dehdashti, Alireza (Frontiers in Public Health, 2022)
Abstract Introduction: SARS-COV2 can have a substantial impact on physical and psychological work demands experienced by nurses in hospital environment. The purpose of this study was to examine personal and work environmental risk factors associated to occupational burnout among hospital nurses. Methods: A cross-sectional study was designed from April to the October 2020.Data from 831 nurses worked professionally in four educational hospitals were compiled through survey questionnaires to report the prevalence of burnout, occupational and individual factors. Independent t-test and Mann-Whitney test to measure the link between the scopes of occupational burnout and personal factors. Results: About half of the participants indicated moderate symptoms of burnout. Nurses’ fear correlated significantly with emotional exhaustion(r= 0.71, p=0.001), depersonalization (r=0.67, p=0.02), and personal accomplishment(r=0.63, p=0.05). Mental demand (r=0.74, p=0.01) and effort at work (r= 0.68, 0.001) correlated significantly with emotional exhaustion (r=0.51, p=0.03). Conclusion: Findings indicated a high prevalence of burnout symptoms particularly emotional exhaustion among hospital nurses. Occupational health services should consider burnout as occupational-related condition and provide interventions to reduce workplace chronic stressors and burnout in hospitals.